2022
DOI: 10.5755/j02.ms.30803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicological Risks of Nail Coatings Containing Acrylate Monomer HEMA

Abstract: Individuals working in nail salons are exposed to 2-hydroxyethyl methacrylate (HEMA). HEMA has been found to have several effects on the skin: skin itching, peeling, redness and allergic contact dermatitis. The purpose of the study was to compare the effects of nail coatings containing HEMA and 2-hydroxypropyl methacrylate (HPMA) on the skin. In this study we explored the irritation properties of HEMA and HPMA containing nail coatings in cell cultures in-vitro and in skin PATCH tests under dermatological contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Summarizing studies from the last 20 years, we found that the most often used ingredient, which can cause these skin reactions, is 2-hydroxyethyl methacrylate (HEMA). These studies showed that compared to the second most used acrylic monomer 2-hydroxypropyl methacrylate (HPMA), HEMA has almost 2 times higher risk of sensitization than HPMA [23]. Our latest research showed that HPMA containing systems are less irritant: cytotoxicity to keratinocyte cell culture was not observed, instead of compositions containing HEMA [23].…”
Section: Introduction *mentioning
confidence: 97%
“…Summarizing studies from the last 20 years, we found that the most often used ingredient, which can cause these skin reactions, is 2-hydroxyethyl methacrylate (HEMA). These studies showed that compared to the second most used acrylic monomer 2-hydroxypropyl methacrylate (HPMA), HEMA has almost 2 times higher risk of sensitization than HPMA [23]. Our latest research showed that HPMA containing systems are less irritant: cytotoxicity to keratinocyte cell culture was not observed, instead of compositions containing HEMA [23].…”
Section: Introduction *mentioning
confidence: 97%